2018
DOI: 10.3168/jds.2017-14043
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the nongenetic causes of variation in the calcium content of bovine milk on French farms

Abstract: Milk is an important source of Ca in Western diets. Milk Ca is important for the cheesemaking process and could be a useful biomarker of Ca regulation in cows. The objective of this study was to identify and quantify nongenetic factors affecting the variation of Ca content in bovine milk. During the PhénoFinLait program, a survey was performed in 3 major areas of milk production in France. This survey consisted of collecting milk samples, together with information about herd management and cow nutrition, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
(70 reference statements)
1
14
1
Order By: Relevance
“…In our study, the range of Ca concentration for all milk samples collected over the experimental period (900-1290 mg/kg, data not shown) was lower in magnitude to that (1110-1470 mg/kg) reported by O'Brien et al (1999), Auldist et al (1999) and Gulati et al (2018). Variations in milk Ca content have been clearly related to the breed, season, stage of lactation, parity, and feed strategy (Nogalska et al 2017;Gaignon et al 2018). In addition, it is well established that the secretion of Ca into milk was regulated by mammary gland secretion of parathyroid hormone-related protein (PTHrP), bone accretion and resorption dynamics, the digestive tract, and kidneys (Boudon et al 2016;Gaignon et al 2018).…”
Section: Calciumcontrasting
confidence: 75%
See 2 more Smart Citations
“…In our study, the range of Ca concentration for all milk samples collected over the experimental period (900-1290 mg/kg, data not shown) was lower in magnitude to that (1110-1470 mg/kg) reported by O'Brien et al (1999), Auldist et al (1999) and Gulati et al (2018). Variations in milk Ca content have been clearly related to the breed, season, stage of lactation, parity, and feed strategy (Nogalska et al 2017;Gaignon et al 2018). In addition, it is well established that the secretion of Ca into milk was regulated by mammary gland secretion of parathyroid hormone-related protein (PTHrP), bone accretion and resorption dynamics, the digestive tract, and kidneys (Boudon et al 2016;Gaignon et al 2018).…”
Section: Calciumcontrasting
confidence: 75%
“…The lower milk Ca content in Tunisian dairy heard was most probably related to the intensive production system based on conserved grass (such as silage or hay), and high quantities of concentrates (Nogalska et al 2017;Gaignon et al 2018).…”
Section: Calciummentioning
confidence: 99%
See 1 more Smart Citation
“…Cows were assigned to the three treatments to allow a homogenous representation of groups and parity within each treatment, and as similar as possible, similar averages of mature equivalent milk production and milk protein contents as observed in the first 32 weeks of the previous lactation. The mature equivalent milk production was estimated as equivalent to milk production for a third lactation cow, i.e., 120% of the milk production for primiparous cows and 104% for cows lactating for a second time, as established from the data used by Gaignon et al (24). Measurement started 3 weeks before the average expected date of calving for each group, on 5 cows of the initial 6, with the extra cow being kept only for blood analyses to replace a cow whose actual calving date might occur too far from the expected date.…”
Section: Methodsmentioning
confidence: 99%
“…VanHouten et al (22) showed that a decrease in Ca intake in mice induced a lower Ca secretion in milk and a higher bone resorption mediated by PTHrP secretion, with both mediated by the Ca-sensing receptor ( CaSR ) in the mammary gland; those results suggest that the monitoring of milk Ca content during lactation could be an inexpensive way to indirectly estimate the dynamics of bone resorption. Mid-infrared spectra technology allows a rapid and inexpensive way to determine the milk Ca content (23,24). Data collected during several stages of lactation in dairy cows with different parities (25) suggested that milk Ca and P contents could be related to the plasma concentrations of biomarker of bone formation and resorption.…”
Section: Introductionmentioning
confidence: 99%